IL-18 in atherosclerosis: context-dependent biology, human evidence, and translational challenges - Dongshuai Zhang; Shuai Wang; Yang Li; Huijie Zhang; Bing Wang (Frontiers in Cardiovascular Medicine, 2026)
Atherosclerosis is a chronic inflammatory disease shaped by interactions among vascular cells, innate immunity, adaptive immunity, and metabolic stress. Interleukin-18 (IL-18), an IL-1 superfamily cytokine activated predominantly downstream of inflammasomes, links vascular injury to type 1 immune responses. This structured narrative review integrates mechanistic, plaque-tissue, epidemiological, genetic, and therapeutic evidence for IL-18 in atherosclerosis. Experimental studies generally support pro-atherogenic actions, but these effects vary by plaque stage, cellular context, and genetic background. Human studies consistently show enrichment of IL-18 in inflamed plaques, whereas circulating IL-18 has limited independent diagnostic or prognostic performance after multivariable adjustment in several large cohorts. Drug-target Mendelian randomization supports associations with selected cardiovascular outcomes, but does not substitute for randomized clinical evidence and remains vulnerable to pleiotropy, instrument strength, ancestry, and lifelong-exposure assumptions. Direct IL-18 inhibitors have entered clinical development in inflammatory diseases, yet cardiovascular outcome efficacy has not been established. We therefore position IL-18 as a biologically plausible but unvalidated cardiovascular target and outline a stage-gated translational agenda centered on free IL-18 assays, plaque-context biomarkers, pharmacology, patient selection, and long-term safety.